XXIII Festival “Zodchestvo in Siberia 2023” - Grigoryeva, Elena (project baikal, 2023)
Siberian architects demonstrate sustainable development in all areas of their work: architecture, urban planning, urbanism, caring for heritage, and education. Not everything goes according to plan, some obstacles have to be overcome, but such is our profession and such is the world.Architects are consistent and stable in their public and competitive activities. Every year, under the auspices of the Union of Architects of Russia, several large festivals take place in Siberia. Each of them has its distinct identity: educational Winter University, skiing Archigesh, youth Archbukhta. “Zodchestvo in Siberia” Festival is the same age as the century, this year it is held for the 23rd time. A few years ago the Festival became nomadic and began to roam around the cities of the Siberian Federal District: Krasnoyarsk, Tomsk, Barnaul, Kemerovo and Novosibirsk have already hosted the Festival. And here we are again in Irkutsk, the birthplace of the Festival. This time we have a unifying theme - the SIBERIAN CODE.
Keywords: Siberian Code; Union of Architects of Russia; Zodchestvo in Siberia